Teenager's Naive Love In William Shakespeare's Romeo And Juliet Drama (1597) : A Psychoanalytic Perspective - RINI, LISTIYO (2012)
The major problem of this study is how the naïve love is reflected in the major character's personality. The aim of this study is to analyze William Shakespeare's, Romeo and Juliet based on the structural elements and the development of personality of the major character based on Psychoanalytic Perspective. This study focuses on the major characters, namely Romeo and Juliet. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the script of the play itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is taking note, while the technique of Data Analysis in this study is descriptive and hermeneutic. Based on the structural analysis it is evident that in this drama, William Shakespeare wants to deliver a message that teenage love is naïve and love can cause death. Based on the psychological analysis, it clear that in Romeo and Juliet play Shakespeare describes a psychological phenomenon, in which the major characters, Romeo and Juliet, have some such qualities as innocent emotion, strong feeling of affection and strong feeling of tenderness.